Hepatitis C virus and human T-cell lymphotropic virus type 1 co-infection: impact on liver disease, virological markers, and neurological outcomes. (April 2017) - Espíndola, Otávio M.; Vizzoni, Alexandre G.; Lampe, Elisabeth; Andrada-Serpa, Maria José; Araújo, Abelardo Q.C.; Leite, Ana Claudia C.
Highlights: The frequency of neurological abnormalities is unaltered during HCV/HTLV-1 co-infection. Hepatic damage is reduced during HCV/HTLV-1 infection, even without HCV clearance. Co-infection with HCV does not change HTLV-1-directed CD4+ T-cell proliferation. HCV-related thrombocytopenia is reversed during co-infection with HTLV-1. Summary: Objectives: Human T-cell lymphotropic virus type 1 (HTLV-1) infection is associated with neurological abnormalities, such as HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP) and peripheral neuropathy (PN). Hepatitis C virus (HCV) infection is the leading cause of chronic liver disease worldwide, and causes PN in approximately 9% of patients. Because the interplay between these potentially neuropathogenic viruses in the same individual is still poorly understood, the clinical and laboratory outcomes of co-infected patients were evaluated and compared with those of controls. Methods: The prevalence rates of neurological and laboratory abnormalities were evaluated in HCV/HTLV-1 co-infected patients ( n = 50), and in subjects with single HCV ( n = 46) or HTLV-1 ( n = 150) infection. Results: A higher frequency of isolated PN was present in HCV-infected patients; this was not associated with cryoglobulinemia. No difference was found in the frequency of PN or HAM/TSP when co-infected subjects were compared to singly infected subjects. Hepatic involvement was present in HCV-infected subjects, as shown by increased levels of serum alanine aminotransferase, aspartate aminotransferase, gamma-glutamyl transferase, and bilirubin, in addition to thrombocytopenia. On the other hand, HCV/HTLV-1 co-infected individuals presented a better prognosis for hepatic involvement when compared with singly HCV-infected subjects. Conclusions: These data suggest that HCV/HTLV-1 co-infection does not mutualistically alter the outcome with regard to neurological manifestations. Nonetheless, changes in the immunological environment induced by HTLV-1 infection could lead to a reduction in hepatic damage, even without significant HCV clearance.